2016
DOI: 10.1080/09540105.2016.1263984
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an immunoaffinity column clean-up for enrofloxacin determination in food samples

Abstract: 2017) Development and application of an immunoaffinity column clean-up for enrofloxacin determination in food samples, Food and Agricultural Immunology, 28:2, 248-259, ABSTRACT Enrofloxacin (ENR) is a synthetic fluoroquinolone antibiotic used for the treatment of infection in animals. The use of ENR has been strictly regulated because of its harmful effect on consumers of animal products. In this study the generation of polyclonal antibody (pAb) against ENR, the preparation of an immunoaffinity chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This effect of enrofloxacin on the intestinal bacterial community may not be long-lasting. However, previous studies have shown that enrofloxacin residues in edible animal products may have adverse effects on humans, such as inducing allergic allergies, reducing sperm count, and diminishing sperm motility ( 54 , 55 ). Therefore, although enrofloxacin exposure did not cause permanent changes in the manure bacterial community, attention should be given to its effects on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of enrofloxacin on the intestinal bacterial community may not be long-lasting. However, previous studies have shown that enrofloxacin residues in edible animal products may have adverse effects on humans, such as inducing allergic allergies, reducing sperm count, and diminishing sperm motility ( 54 , 55 ). Therefore, although enrofloxacin exposure did not cause permanent changes in the manure bacterial community, attention should be given to its effects on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, instrumental analysis based on chromatographic separation techniques [ 13 , 14 ] and immunoassays [ 15 , 16 ] based on antigen (Ag)-antibody (Ab) binding are the major analytical methods for ENRO measurement in food samples. In our previous studies, we prepared a molecularly imprinted biomimetic material [ 17 ] and polyclonal Ab with specific ability to recognize ENRO and developed relative instrumental and immunoassays/products for ENRO residue detection in food products.…”
Section: Introductionmentioning
confidence: 99%